1H-Pyrrole-2,5-dicarboxylic acid, a quorum sensing inhibitor from one endophytic fungus in Areca catechu L., acts as antibiotic accelerant against Pseudomonas aeruginosa - Liu, Junsheng; Wang, Zhennan; Zeng, Yuexiang; Wang, Wei; Tang, Shi; Jia, Aiqun (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa has already been stipulated as a “critical” pathogen, emphasizing the urgent need for researching and developing novel antibacterial agents due to multidrug resistance. Bacterial biofilm formation facilitates cystic fibrosis development and restricts the antibacterial potential of many current antibiotics. The capacity of P. aeruginosa to form biofilms and resist antibiotics is closely correlated with quorum sensing (QS). Bacterial QS is being contemplated as a promising target for developing novel antibacterial agents. QS inhibitors are a promising strategy for treating chronic infections. This study reported that the active compound PT22 (1H-pyrrole-2,5-dicarboxylic acid) isolated from Perenniporia tephropora FF2, one endophytic fungus from Areca catechu L., presents QS inhibitory activity against P. aeruginosa. Combined with gentamycin or piperacillin, PT22 functions as a novel antibiotic accelerant against P. aeruginosa. PT22 (0.50 mg/mL, 0.75 mg/mL, and 1.00 mg/mL) reduces the production of QS-related virulence factors, such as pyocyanin and rhamnolipid, and inhibits biofilm formation of P. aeruginosa PAO1 instead of affecting its growth. The architectural disruption of the biofilms was confirmed by visualization through scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Real-time quantitative PCR (RT-qPCR) indicated that PT22 significantly attenuated the expression of QS-related genes followed by docking analysis of molecules against QS activator proteins. PT22 dramatically increased the survival rate of Galleria mellonella. PT22 combined with gentamycin or piperacillin presents significant inhibition of biofilm formation and eradication of mature biofilm compared to monotherapy, which was also confirmed by visualization through SEM and CLSM. After being treated with PT22 combined with gentamycin or piperacillin, the survival rates of G. mellonella were significantly increased compared to those of monotherapy. PT22 significantly enhanced the susceptibility of gentamycin and piperacillin against P. aeruginosa PAO1. Our results suggest that PT22 from P. tephropora FF2 as a potent QS inhibitor is a candidate antibiotic accelerant to combat the antibiotic resistance of P. aeruginosa.